Pembinaan Kompetensi Kuantitatif Siswa untuk Persiapan UTBK bagi Siswa MA Arrahman Jombang - Indana Lazulfa; Anita Andriani; Iftitaahul Mufarrihah (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2022)
Scholastic Potential Test (TPS) material training is needed to prepare for tests at post-high school level. In Indonesia, TPS is widely used for tests such as a test of university entrance selection, test of job recruitment, and the scholarship test. TPS is also used to measure a person’s intelligence. One of the phenomena that occurred in high school in Jombang was that there is no TPS material lesson, especially in 11th or 12th grade. This happened because it followed the school curriculum.So, students will be less prepared for their tests. This training aims to introduce and train students to solve on various types of TPS questions. The materials include general reasoning, quantitative knowledge, and general knowledge. The result of this training is 80% of the participants were able to improve their post-test score. The method which had been used in this training consists of several stages like observation, requirement analysis, design, material development, training, and evaluation. Result of this training is an increase in student test scores after training. Post-test score shows an increase in the number of participants who passed a passing grade by 30% from the previous one. So, total of 70% of the participants or about 28 trainees were able to pass the passing grade.